PTH-187 Treatment of barrett's early neoplasia (EN) in the UK: results of a survey of gastroenterologists and upper GI surgeons. (22nd June 2015) - De Caestecker, JS; Stokes, C; Barr, H; Smart, HL; Lovat, L; Ragunath, K; Bhandari, P; Budihal, S
Abstract : Introduction: Oesophagectomy (S) and endoscopic treatment (ET – endoscopic resection [ER] &/or ablation) for Barrett's Early Neoplasia (EN) are both established options but have never been directly compared. Method: An e mail questionnaire was sent to consultant upper GI surgeon AUGIS members and UK BOSS trial PIs to establish attitudes towards S and ET and explore feasibility of a trial to compare them. A number of clinical scenarios were presented. Results: There were 70 responses (29 surgeons, 40 physicians, 1 not stated). In response to the question 'How should Barrett's EN be treated?' most (52%) felt there was a role for both S and ET, with 3% favouring S and 45% ET. Most (86%) felt it depended on the scenario: some centres routinely discuss surgery as an option. Several scenarios were presented. For HGD patients unfit for S, 49% felt patients should have ET, 2% surveillance, 49% gave 2 or 3 options including 24% no treatment. In a patient fit for S 83% felt ET was the treatment of choice if unifocal (after staging ER if visible abnormality) but 17% opted for S, especially in young patients. For multifocal HGD, 44% favoured S (an additional 13% after staging ET) and 43% ET. Scenarios relating to T1 tumours fit for surgery were presented: for 91%, choice of treatment depended on histology of staging ER. 97% favoured ET (3% S) for T1a (m 1 –3). Several commented on importance of tumour differentiation and lymphovascular invasion for decision. For T1b (sm1), 39% favoured S, 12% ET, 49% unsure (several commented that patient preference and age were important factors). 76% believed that an RCT comparing S to ET is needed to inform future practice, but among dissenters were comments: 'difficulty in blinding/numbers needed', 'too late as endoscopy already established and observational data convincing', 'unethical for trial'. 70% thought such a trial might be possible in the UK. In terms of what types of patients respondents might be prepared to offer entry into such a trial, patients with multifocal HGD, T1a (m 1 –3) or T1sm1 tumours had the highest support for inclusion, while patients with flat/ unifocal HGD had the least. Conclusion: This snapshot of UK current opinion and practice shows that for patients with HGD (if unifocal) and T1a cancers with histologically good prognostic features ET is preferred by most respondents. Most disagreement was for patients with multifocal HGD and T1b (sm1) cancers. Both these and T1a cancers were the most strongly supported for an RCT comparing S and ET. Disclosure of interest: None Declared.